Perkembangan Asuransi Jiwa Syariah Di Indonesia - Susi Kusmawaningsih (Lembaga Pengembangan Keilmuan, Penelitian dan Pengabdian Masyarakat (LP3M), Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2022)
Sharia insurance is an insurance business field that has received considerable attention among the people of Indonesia today. As an alternative business, sharia insurance is relatively new to develop in Indonesia. This is enough to attract the attention of the insurance business world in line with the rapid development of the sharia banking business. Sharia insurance is an insurance business field that has received great attention among the people of Indonesia. As an alternative insurance business, Islamic insurance is relatively new compared to the conventional insurance business. The novelty of the sharia insurance business is the operation of its business activities based on sharia principles sourced from the Koran and hadith as well as the Fatwas of the Ulama, especially those collected in the Indonesian Ulema Council (MUI). The principle that distinguishes sharia insurance from conventional insurance is that sharia insurance eliminates elements of uncertainty (gharar), elements of speculation or gambling (maisir), and elements of interest (riba) in their business activities so that insurance participants (insured) feel free from tyrannical practices that harm them. The reason for establishing sharia insurance is because the majority of Indonesians are Muslim, consider the implementation of conventional insurance that already exists is not in accordance with sharia principles because it contains elements of obscurity (gharar), contains elements of gambling (maisir), and contains elements of interest money (riba). The material legal sources of sharia insurance are Islamic sharia, while the sources of Islamic sharia are the Koran, Hadith, Ijma (Ijtihad), Fatwa of the Companions of the Apostles, Qiyas, Istihsan, and Urf (tradition), the Koran and Hadith are the main sources of Islamic law, but in setting the principles -principles and practices and operations of sharia insurance, the parameter that is always a reference is Islamic sharia. The concept of sharia insurance is based on the Qur'an Surah Almaaidah verse (2) which means: